2020
DOI: 10.1158/1538-7445.sabcs19-p1-20-01
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P1-20-01: Primary surgery in patients with de novo stage IV BC; finalizing the protocol MF07-01 randomized clinical trial

Abstract: This paper presents an experimental characterization of the effects of earthquakes on the operation of mechanical systems with the help of CaPaMan (Cassino Parallel Manipulator), which is a 3 DOF robot that can fairly well simulate 3D earthquake motion. The sensitivity of operation characteristics of machinery to earthquake disturbance is identified and characterized through experimental tests. Experimental tests have been carried out by using a slider-crank linkage, a small car model, and LARM Hand as test-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This group recently presented updated results at the San Antonio BC Symposium in 2019. 20 This final analysis showed significant 10-year OS benefit with LRT, 46 months vs 35 months, HR = 0.71. This study looked at many prognostic factors including LRT, hormone receptor positivity, disease burden, and sites of metastases.…”
Section: Prospective Studiesmentioning
confidence: 76%
“…This group recently presented updated results at the San Antonio BC Symposium in 2019. 20 This final analysis showed significant 10-year OS benefit with LRT, 46 months vs 35 months, HR = 0.71. This study looked at many prognostic factors including LRT, hormone receptor positivity, disease burden, and sites of metastases.…”
Section: Prospective Studiesmentioning
confidence: 76%
“…Several studies have suggested that by obtaining loco-regional control in metastatic breast cancer, overall survival in advanced disease would be improved. [9][10][11] However, randomised controlled trials have contradicted this. 12 13 A recent presentation at ASCO 2020 14 confirmed that local treatment in addition to systemic therapy did not improve survival.…”
Section: Introductionmentioning
confidence: 99%